1994
DOI: 10.1177/107110079401500409
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Visualization of the Tibial Plafond During Posterior Malleolar Fracture Fixation

Abstract: Fracture of the tibial plafond, such as in a trimalleolar fracture, with a large posterior tibial (posterior malleolus) fragment may require open reduction and internal fixation. Anatomic reduction of the articular surface can be ensured by visualizing the articular surface using an arthroscope during reduction. Four cases wherein this technique has proven effective are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 4 publications
0
12
0
1
Order By: Relevance
“…Several authors reported an incidence of intraarticular pathology in ankle fractures ranging between 63% and 79.2% [22,30]. Based on the minimal added time and morbidity to the surgical procedure, we use arthroscopy on a regular basis in intraarticular fractures [23,25,33].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported an incidence of intraarticular pathology in ankle fractures ranging between 63% and 79.2% [22,30]. Based on the minimal added time and morbidity to the surgical procedure, we use arthroscopy on a regular basis in intraarticular fractures [23,25,33].…”
Section: Discussionmentioning
confidence: 99%
“…Despite being first described by Holt in 1994 10 and a general positive experience from adopter publications, there is a dearth of research and documentation on arthroscopic reduction and internal fixation of posterior malleolar fractures 5 . In our experience, we have found this to be reliable technique to restore articular congruity and ankle stability in posterior malleolar fractures.…”
Section: Discussionmentioning
confidence: 73%
“…This approach has limited visualization of the posterior malleolus fragment. Holt (13) described an arthroscopically assisted reduction of the posterior malleolus. Weber (12) described a case series of 9 patients who were treated with a combined posteromedial and posterolateral approach.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect reduction with stabilization of the posterior malleolus using anteroposterior screws is the most common method of fixation of the posterior malleolus among orthopedic surgeons (8,9). Different approaches have been described for fixation of the posterior malleolus (9)(10)(11)(12)(13)(14). Recently, interest has been growing in obtaining direct reduction and fixation of the posterior malleolus from the posterior surface using a posterolateral approach to the ankle (7,(14)(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%